Faktor-Faktor Yang Berhubungan Dengan Waktu Reaksi Rangsang Cahaya Pada Tenaga Kerja Yang Terpapar Panas Di PT. Baja Kurnia Ceper Klaten - Handayani, Sri; Suhartono, Suhartono; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2005)
ABSTRACT Background : One of the negative impacts from the iron work industry is heat in working environment. The heat stress in the working environment gives the workers additional burden and may result an adverse health effect, especially the metabolism of  their body.  Consequently, it may couse fatigue that causes the decrease of their working productivity. The fatigue may be clearly observed on the basis of the measurement of reaction time of light stimuli. The study aims for determining factors related to reaction time of light stimuli of the employees exposed to heat in PT. Baja Kurnia Ceper, Klaten. Method : The study used  cross sectional approach. The samples of the study were 43 workers. It was conducted on January – May 2005. Data was collected using measurement of ambient temperature in the production room, measurement of the fatigue with the reaction time of light stimuli, counting of arterial pulse, measurement of body weihgt/high and interview with respondent. Data was analyzed by using Pearson Product Moment Corelation, Independent t-Test and Multiple Linier Regression Result : Result of the study indicated that ambient temperature was 30,640C, age was 34,35 on average, nutritional status 19,89 on average, working periode was 8,23 on average, the pre-working of reaction time of light stimuli was 352,46 mmdet on average, and the post-working of reaction time of light stimuli was 500,78 mmdet on average, while 27 employees were in the condition of helath dan 16 employees were in the condition of not helath. Conclusion : There was a significant correlation between ambient temperature, age, nutritional status,  working periode, working burden and reaction time of light stimuli. There was not  any defference in reaction time of light stimuli in the group pf health respondents andthat of not health respondents. Key words : temperature, nutrional status, working burden, light stimuli